cos2a=cos(a+a)=cosa*cosa-sina*sina=(cosa)^2-(sina)^2=[1-(sina)^2]-(sina)^2=1-2(sina)^2
=(cosa)^2-[1-(cosa)^2]=2(cosa)^2-1
cos(a-b)=cos[a+(-b)]=cosa*cos(-b)-sina*sin(-b)=cosa*cosb+sina*sinb
sin(a-b)=-cos[π/2+(a-b)]=-cos[(π/2-b)+a]=-[cos(π/2-b)*cosa-sin(π/2-b)*sina]
=-(sinb*cosa-cosb*sina)=sina*cosb-sinb*cosa
sin(a+b)=-cos[π/2+(a+b)]=-cos[(π/2+a)+b]=-[cos(π/2+a)*cosb-sin(π/2+a)*sinb]
=-(-sina*cosb-cosa*sinb)=sina*cosb+cosa*sinb
sin2a=-cos(π/2+(a+a)) =-cos[(π/2+a)+a]=-[cos(π/2+a)*cosa-sin(π/2+a)*sina]
=-(-sina*cosa-cosa*sina)=2sina*cosa
太多了- -耐心用完.你将就着用吧.